2011
DOI: 10.1186/1471-2148-11-130
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of plasmid-carried antibiotic resistance

Abstract: BackgroundAntibiotic resistance represents a significant public health problem. When resistance genes are mobile, being carried on plasmids or phages, their spread can be greatly accelerated. Plasmids in particular have been implicated in the spread of antibiotic resistance genes. However, the selective pressures which favour plasmid-carried resistance genes have not been fully established. Here we address this issue with mathematical models of plasmid dynamics in response to different antibiotic treatment reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
117
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(124 citation statements)
references
References 54 publications
4
117
0
3
Order By: Relevance
“…The presence of multiple plasmids may support the high resistance profile against a range of antibiotic as plasmid borne resistance is common in many microbes. It is well reported that antibiotic resistance is often plasmid borne (Svara and Rankin, 2011). Our results get support from Aslim and Beyatli (2004) who reported higher antibiotic resistance in the isolates carrying multiple plasmids.…”
Section: Discussionsupporting
confidence: 90%
“…The presence of multiple plasmids may support the high resistance profile against a range of antibiotic as plasmid borne resistance is common in many microbes. It is well reported that antibiotic resistance is often plasmid borne (Svara and Rankin, 2011). Our results get support from Aslim and Beyatli (2004) who reported higher antibiotic resistance in the isolates carrying multiple plasmids.…”
Section: Discussionsupporting
confidence: 90%
“…In keeping with previous studies9141819 a system of coupled ordinary differential equations are used to describe the dynamics of a population of susceptible (S) and resistant (R) bacteria. As asexual reproduction requires energy it is assumed that the growth rate of bacteria is limited and therefore modelled using the standard logistic growth equation.…”
Section: Modelmentioning
confidence: 99%
“…While mutations are undoubtedly a source of resistance, HGT is responsible for increased propagation of resistance through bacterial populations8. If bacteria acquire resistant genes in an environment where they are beneficial, HGT will facilitate the spread of these genes within the population9. Sub-Minimum Inhibitory Concentrations (MIC) of antibiotics and the persistence of high levels of antibiotics within the environment have been linked to the emergence of resistant genes1011.…”
mentioning
confidence: 99%
“…It manifests the increase of infection or the prolonged clinical symptomatology, increase in hospital stay, and not less important, the rise of costs to the health system (Coculescu, 2009; Edgar et al , 2009; Högberg et al , 2010; Huttner et al , 2010; Kurek et al , 2011; Savara and Rankin, 2011; Wilke, 2010). …”
Section: Antibiotic Resistance: Social Economical and Biological Aspmentioning
confidence: 99%